Penayangan Acara Supranatural di Media Televisi (Tinjauan Hukum Islam) - Wali, Rujum; Kabalmay, Husin Anang; Maswara, Husen (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Supernatural shows are a type of film that is played on television media and contains mystical elements in it. The airing of supernatural shows so far contains many elements that are not educational, because many scenes are not suitable for airing. The purpose of this study is to determine the efforts to broadcast supernatural programs that develop on television media in terms of Islamic law and its impact on society. The type of research used in this study is using the type of library research (Library Research), which is research carried out by reviewing and analyzing books, scientific papers, journals, and articles of a scientific nature. Based on the results of data analysis, it was found that the process of airing supernatural shows on television media when viewed from Islamic law, then the process of airing is prohibited. Because. Supernatural shows aired on television media have a negative impact both in terms of psychology of people who watch them and from a social perspective. In terms of psychology, the airing of supernatural shows has an impact on the emergence of fear in a person and can affect child development. While from a social point of view, the process of airing supernatural shows affects the Islamic creed, namely one's belief in Allah can be disrupted and begin to obscure